If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + y)(3x + 5y) = 0 Multiply (2x + y) * (3x + 5y) (2x * (3x + 5y) + y(3x + 5y)) = 0 ((3x * 2x + 5y * 2x) + y(3x + 5y)) = 0 Reorder the terms: ((10xy + 6x2) + y(3x + 5y)) = 0 ((10xy + 6x2) + y(3x + 5y)) = 0 (10xy + 6x2 + (3x * y + 5y * y)) = 0 (10xy + 6x2 + (3xy + 5y2)) = 0 Reorder the terms: (10xy + 3xy + 6x2 + 5y2) = 0 Combine like terms: 10xy + 3xy = 13xy (13xy + 6x2 + 5y2) = 0 Solving 13xy + 6x2 + 5y2 = 0 Solving for variable 'x'. Factor a trinomial. (2x + y)(3x + 5y) = 0Subproblem 1
Set the factor '(2x + y)' equal to zero and attempt to solve: Simplifying 2x + y = 0 Solving 2x + y = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y' to each side of the equation. 2x + y + -1y = 0 + -1y Combine like terms: y + -1y = 0 2x + 0 = 0 + -1y 2x = 0 + -1y Remove the zero: 2x = -1y Divide each side by '2'. x = -0.5y Simplifying x = -0.5ySubproblem 2
Set the factor '(3x + 5y)' equal to zero and attempt to solve: Simplifying 3x + 5y = 0 Solving 3x + 5y = 0 Move all terms containing x to the left, all other terms to the right. Add '-5y' to each side of the equation. 3x + 5y + -5y = 0 + -5y Combine like terms: 5y + -5y = 0 3x + 0 = 0 + -5y 3x = 0 + -5y Remove the zero: 3x = -5y Divide each side by '3'. x = -1.666666667y Simplifying x = -1.666666667ySolution
x = {-0.5y, -1.666666667y}
| 15x^2+10=0 | | -4.5q+1.7=-25.8-2q | | 4x^2-23x-11=0 | | (b-8)/(8b-16) | | 8x-12+3x-21=4.5 | | S=5k+5vfork | | 4(1+3n)=8(n+5) | | 3p^2+10p+8=0 | | 8(1-4b)-(7b+8)=-4b-5b | | 233=33+x-22 | | 4x+3=68+x-1 | | 4p+5p+1=0 | | 8w-8+8=48+8 | | axb=-36 | | (-x-4)=6(9+6x)-206 | | 3(-9x-5)=3+3(8-7x) | | y^3=-25y | | -4(6-4x)=168+(8-9x) | | 9(5x-9)=7(3+4x)-153 | | 50000=300/x | | 4x-6=-32 | | 2x+14+3x-15=7 | | 5(t+2)=2(t+3) | | (2x-7)(x+3)(x-2)=0 | | (4x)+(3x-8)=90 | | x+x-20=54 | | 2x^2+2y^2+8x-12y+3=0 | | 8y+3=7y-7 | | 20-5/2 | | j^2+24j+23=0 | | 2(x-3)-4x=8-3(2x-1)+11 | | 2x+16=3x-25 |